Multiphasic Computed Tomography Enhancement Characteristics and Utility of Delayed Phase in Infiltrative Hepatocellular Carcinoma - Tarvinder Singh; Nandita Mehta; Pankaj Gupta; Ajay Gulati; Mudita Gulati; Naveen Kalra; Madhumita Premkumar; Sunil Taneja; Vaneet Jearth; Vishal Sharma; Ajay Duseja (Indian Journal of Radiology and Imaging)
Objective The aims of this study are to compare the multiphasic contrast-enhanced computed tomography (CECT) characteristics of infiltrative hepatocellular carcinoma (HCC) with nodular HCC and to assess the conspicuity of infiltrative HCC on different phases of CECT.